The role of obesity in structural and functional characteristics of left cardiac chambers. (14th October 2021) - Trofimova, E; Bogdanova, A; Konstantinova, E; Bogdanov, A; Gilyarov, M
Abstract: Purpose of study: To evaluate the role of obesity in structural and functional characteristics of left cardiac chambers according to the echocardiographic study. Materials and methods: The retrospective analysis of 1760 echocardiographic studies in patients 30–65 years old with hyperlipoproteinemia IIa and IIb types was evaluated. The body mass index (BMI) of the patients varied from normal to morbid obesity. Results: The achieved results showed positive correlation between structural and functional heart characteristics and BMI. Anteroposterior size and BMI reliable correlated (KK=0, 70, p<0, 05). In obese patients the thickness of left ventricular wall increased in 20% (1, 25±0, 15sm), compared to 1, 0±0, 19sm in patients with normal weight. The thickness of interventricular wall raised from 1, 02±0, 15sm to 1, 23±0, 14sm. End-diastolic volume in obese patients was higher than in normal weight patients (70±16 and 123±32, 3sm 3 ). End-systolic volume of left ventricle grows to 45% (from 30±8, 5 to 54, 3±20, 5sm 3 ). Impact volume in patients with obesity increased from 52±9, 8 ml to 68, 4±15, 0ml. In patients with BMI 25–39.9kg/m 2 the left ventricle mass myocardium index raised in 10%, and in patients with BMI over 40kg/m 2 – more than 20%. Concentric remodeling of left ventricle was found in 28, 18% women and 43, 39% men with normal BMI, in 30, 76% women and 34, 12% men with obesity, and in 15, 9% women and 15, 26% men with morbid obesity. Concentric hypertrophy of left ventricle wall was diagnosed in 10% women and 10, 74% men with normal BMI, in 33, 38% women and 32, 4% men with obesity and in 59, 36% women and 54, 82% men with morbid obesity. Eccentric hypertrophy of left ventricle wall was diagnosed in 4, 61% women and 2, 89% men with normal BMI, in 9, 42% women and 16, 74% men with obesity and in 14, 87% women and 25, 9% men with morbid obesity. The proportion of women with normal LV geometry decreased more than 6 times as obesity progressed, proportion of men decreased by 9 times. Conclusions: Thus, the typical presentation of structural and functional changes in the left heart chambers of obesity is the combination of concentric hypertrophy and/or remodeling of LV myocardium, diastolic LV dysfunction and dilatation of the left atrium. All these changes are the basis for the formation of dilated cardiopathy in obesity. FUNDunding Acknowledgement: Type of funding sources: None.